1999
DOI: 10.1046/j.1365-2044.1999.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambient pressure oxygen reservoir apparatus for use during one‐lung anaesthesia

Abstract: SummaryAn ambient pressure oxygen reservoir bag apparatus for connecting to the nonventilated lung as soon as single-lung ventilation is initiated is described. The theoretical benefits are the facilitation of collapse of the lung on the side of surgery and a reduced likelihood of arterial desaturation. Although these main benefits are yet to be proven, the authors believe that the weight of theoretical argument and practical observation serves to justify the use of the apparatus while the outcome of suitably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…7 Although one report showed that a low level of CPAP is effective at reversing the hypoxemia and provides a good surgical field, the study was confined to open thoracic surgery. 8 Intermittent positive pressure, 9 selective segmental lung insufflations, 10 and apneic oxygenation [11][12][13][14] have been introduced as alternatives to CPAP; however, reports on these methods have limitations because they are preliminary studies, [9][10][11][12][13][14] include a small number of cases, [9][10][11] or are noncontrolled and nonrandomized trials. [9][10][11]13,14 Therefore, to date, no generally accepted replacement or supplementary method for CPAP is available in hypoxic situations during OLV.…”
Section: Perspectivementioning
confidence: 99%
“…7 Although one report showed that a low level of CPAP is effective at reversing the hypoxemia and provides a good surgical field, the study was confined to open thoracic surgery. 8 Intermittent positive pressure, 9 selective segmental lung insufflations, 10 and apneic oxygenation [11][12][13][14] have been introduced as alternatives to CPAP; however, reports on these methods have limitations because they are preliminary studies, [9][10][11][12][13][14] include a small number of cases, [9][10][11] or are noncontrolled and nonrandomized trials. [9][10][11]13,14 Therefore, to date, no generally accepted replacement or supplementary method for CPAP is available in hypoxic situations during OLV.…”
Section: Perspectivementioning
confidence: 99%
“…[15] No operating should be conducted with oxygen saturations of less then 90%. The safe position always is ventilation of both lungs and 100% oxygen.…”
Section: Consequences Of Olvmentioning
confidence: 99%
“…Over recent years, there has developed amongst anaesthetists a reluctance to be open‐minded about any clinical practice that is not ‘evidence‐based’ or not widely accepted. In the area of one‐lung anaesthesia, for instance, one practice that is yet to be widely embraced is the use of an ambient pressure oxygen reservoir attached to the non‐ventilated lung [1, 2], even though the resulting exclusion of atmospheric nitrogen will almost certainly hasten lung collapse and so facilitate thoracoscopic surgery. It will very likely also reduce the risk of arterial desaturation [3].…”
mentioning
confidence: 99%
“…Another of the several suggested benefits [1, 4–6], is the ability to identify gas leaking past the endobronchial cuff of the double‐lumen tube. If the leak is large, the reservoir bag will be seen to progressively fill with each inspiratory phase of single‐lung ventilation, but smaller leaks may not be so immediately obvious.…”
mentioning
confidence: 99%
See 1 more Smart Citation